Can gender be a determinant of organizational performance and knowledge sharing in public sector organizations? (2018)
The objective of this scientific article is to determine if gender affects the relationship between organizational performance and knowledge sharing in public sector organizations. Based on the literature review and drawing from the theoretical perspective of a resource-based view, the research hypotheses were formulated. Through a cross-sectional study, of ten Mexican organizations from the public sector and through the perception of 239 public servants, these hypotheses were tested. A linear regression analysis was performed. The results confirm the importance of gender as a determinant variable in the management and administration of the organizations. This research also shows that the intervening management of valuable resources (knowledge) helps to generate strategies (organizational performance) that have no cost for public sector organizations.